2022
DOI: 10.1111/dpr.12581
|View full text |Cite
|
Sign up to set email alerts
|

Kenya’s informal milk markets and the regulation–reality gap

Abstract: Summary Motivation Around 80% of milk in Kenya is marketed informally, providing livelihoods and contributing to the food security and nutrition of low‐income consumers. Government policy, however, is focused on formalization—primarily through licensing and pasteurization—with enforcement via fines, confiscation of milk, or closing the premises of informal actors. Purpose This article seeks to better understand if, and why, Kenya’s informal milk sector and regulatory system are disconnected from one another an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…Moreover, our results show that producers, intermediaries and vendors are concerned about milk safety and take measures to ensure food safety such as cleaning their containers regularly, washing their hands and keeping their premises clean. This is consistent with evidence from Kenya (Blackmore et al, 2021) and South Africa (Campbell, 2011), where street vendors were found to have adequate information regarding food safety principles and to ensure safe practices in food preparation.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Moreover, our results show that producers, intermediaries and vendors are concerned about milk safety and take measures to ensure food safety such as cleaning their containers regularly, washing their hands and keeping their premises clean. This is consistent with evidence from Kenya (Blackmore et al, 2021) and South Africa (Campbell, 2011), where street vendors were found to have adequate information regarding food safety principles and to ensure safe practices in food preparation.…”
Section: Discussionsupporting
confidence: 87%
“…In practice this means that informal milk trade exists and persists without government interference. This sets it apart from the adversarial relationships between regulators and informal actors found in several other low-and middle-income countries, whose contexts are defined by harassment, forced relocations, confiscation of goods, and physical abuse (Patel et al, 2014;Resnick, 2017;Grace et al, 2019;Young and Crush, 2019;Blackmore et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations